Social and Moral Criticism in Satirical Verses: Analysis Using the Maudhūʿī and Linguistic Approaches - Masruchin Masruchin (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2025)
The recurring phenomenon of social deviance and moral degradation in society confirms the relevance of studying verses in the Qur'an that contain social criticism in the form of satire. This article aims to analyze social and moral criticism in satirical verses of the Qur'an using a maudhūʿī (thematic) approach and linguistic analysis (rhetoric, pragmatics, and critical discourse). This is a qualitative study analyzing four representative surahs, al-Maʿūn (107:1–7), al-Mutaffifīn (83:1–3), al-Humazah (104:1–9), and al-Munāfiqūn (63:1–3), selected based on their rhetorical power in criticizing deviant behavior. The results show that the Qur’an uses rhetorical devices such as irony, repetition, contrast, and labeling to shame hypocritical, materialistic, and anti-social behavior; for example, Surah al-Maʿūn emphasizes the contrast between ritual piety and social negligence, while Surah al-Mutaffifīn criticizes economic injustice through irony. These findings show that Qur'anic satire not only functions as a moral admonition, but also as an instrument of social discourse that builds collective awareness of justice, caring, communication ethics, and spiritual integrity. This study enriches thematic exegesis by offering a linguistic perspective on reading the function of Qur'anic satire an approach that has been relatively rare in previous studies.